1999
DOI: 10.1093/ajcn/70.6.976
|View full text |Cite
|
Sign up to set email alerts
|

Are olive oil diets antithrombotic? Diets enriched with olive, rapeseed, or sunflower oil affect postprandial factor VII differently

Abstract: A background diet rich in olive oil may attenuate the acute procoagulant effects of fatty meals, which might contribute to the low incidence of IHD in Mediterranean areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
3
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 29 publications
10
72
3
2
Order By: Relevance
“…These fatty acids were significantly (P<0.05) higher in P. littoralis than in U. terminalis, and oleic acid has been attributed health-giving properties due to monounsaturated status (Larsen et al, 1999). Similarly, to our finding, Vernocchi et al (2007) reported that the oleic acid and palmitoleic acid levels for M. galloprovincialis captured from Adriatic Sea were 2.34-6.34% and 9.88-36.33%, respectively.…”
Section: Resultssupporting
confidence: 78%
“…These fatty acids were significantly (P<0.05) higher in P. littoralis than in U. terminalis, and oleic acid has been attributed health-giving properties due to monounsaturated status (Larsen et al, 1999). Similarly, to our finding, Vernocchi et al (2007) reported that the oleic acid and palmitoleic acid levels for M. galloprovincialis captured from Adriatic Sea were 2.34-6.34% and 9.88-36.33%, respectively.…”
Section: Resultssupporting
confidence: 78%
“…Moreover, plant oil sources of these fatty acids, e.g. flaxseed (Nelson & Chamberlain, 1995), rapeseed (Bierenbaum et al 1991;de Lorgeril et al 1994) and olive Larsen et al 1999) oils exert a positive impact on cardiovascular risk factors in man. Thus, plant oils containing relatively low concentrations of 18 : 2n-6, and concomitantly higher levels of 18 : 1n-9 and/or 18 : 3n-3, may emerge as health-promoting food choices on the basis of both cardiovascular benefits and capacity to reduce the risk of opportunistic infection.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that a Mediterranean diet reduces fasting plasma concentrations of FVIIa in healthy men (5), a fact that might be related to the presence of olive oil in this diet (6,7). Williams (8) observed a reduction in postprandial FVIIa and factor VII antigen (FVIIag) plasma concentrations after the acute intake of an olive oil-based meal.…”
Section: Introductionmentioning
confidence: 99%